Technology Dissemination of Smart Tani Fish Farmers in Karang Kepanjen Hamlet, Trimulyo Village, Sleman District, Sleman Regency - Iswanto Suwarno; Nia Maharani Raharja; Dhiya Uddin Rijalusalam; Rachmad Andri Atmoko; Irfan Ahmad; Israa Al_barazanchi; Sashikala Mishra (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
Smartani "Fish Farming SMEs" is located in an agricultural area in Sleman Regency, precisely in Karang Kepanjen Hamlet, Trimulyo Village, Sleman District, Sleman Regency, Yogyakarta Special Region has been conducting tilapia cultivation activities since 2012. Smartani fishery cultivation is led by Mr. Bondan Widoropexy. In fact, Mr. Bondan Widoropeksi has a large enough market opportunity for aquaculture. However, this opportunity brings consequences and problems, namely the lack of a touch of innovation from the fish feeding system. Information about some of the problems faced by fish farming must be addressed as soon as possible as a solution for developing aquaculture business. Through this proposed science and technology activity program and based on the needs analysis that has been carried out, the service team tries to offer solutions to these problems with a touch of science and technology, namely through the main activity of designing remote fish feeders with IoT technology. This remote fish feed technology uses Arduino type microcontroller technology which is equipped with remote communication technology using GSM modules. The schedule of fish feeders and the dose of the amount of feed needed by the fish can be set automatically and remotely using IoT technology.